2000
DOI: 10.1042/bj3490135
|View full text |Cite
|
Sign up to set email alerts
|

The short prodomain influences caspase-3 activation in HeLa cells

Abstract: Proteolytic activation of caspases is a key step in the process of apoptosis. According to their primary structure, caspases can be divided into a group with a long prodomain and a group with a short prodomain. Whereas long prodomains play a role in autocatalytic processing, little is known about the function of the short prodomain, for example the prodomain of caspase-3. We constructed caspase-3 variants lacking the prodomain and overexpressed these in HeLa and yeast cells. We found that removal of the caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrated in a cell-free system that there are two cleavage events to form the p17 and p12 subunits 10 . While one study concluded that removal of the prodomain resulted in a constitutively active caspase-3 15 , others have demonstrated that the prodomain does not influence apoptotic activity 22 . These studies expressed caspase-3 transiently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated in a cell-free system that there are two cleavage events to form the p17 and p12 subunits 10 . While one study concluded that removal of the prodomain resulted in a constitutively active caspase-3 15 , others have demonstrated that the prodomain does not influence apoptotic activity 22 . These studies expressed caspase-3 transiently.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic activity of caspase-3 is well characterized, but the regulation of this process is not fully understood. Previous studies demonstrated that the complete removal of the prodomain enhances apoptotic activity 15 . However, it is unknown whether this induction results in complete activation of caspase-3 or lowers the activation threshold.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of short prodomains, found on caspases 3, 6, 7, and 14, is unclear. It is possible that they serve as intermolecular recognition sites, as subcellular localization signals, or as regulators of caspase activity (14–16). Regardless of the type, however, the prodomain is removed during proteolytic processing, and the remaining molecule is further cleaved into large (p20) and small (p10) subunits.…”
Section: The Road To Destructionmentioning
confidence: 99%